Academic dishonesty in online English as a Foreign Language classroom - Wahyu Indah Mala Rohmana; Shofia Kamal; Nailatul Amani; Tazkia Adiba As-Samawi (Universitas Merdeka Malang, 2022)
In spite of studies about academic dishonesty that have been conducted by many researchers, only a small number of studies have investigated academic integrity in online EFL classrooms at university level. The aim of this research is to seek about the occurrence and types of academic dishonesty as well as strategies that could be used by English teachers to overcome the problem. This research investigated the reason why EFL students tend to carry out academic dishonesty in online learning. Researchers used open-ended questions to gain the students opinion and responses. Rresults of this research shows that 55.6% of the respondents understood what was considered to be academic dishonesty and in the same percentage they also sometimes conducted academic dishonesty. In exam related violations, 61.1% of them sometimes looked up information on the web to get helps or answers. In assignment related violation, 38.9% responded that they sometimes shared answers of the task and collaborated with others on individually assigned work. In online session related violations, 38.9% showed that sometimes they participated in a live session from one device and did other activities at the same time. Then, reasons why they did academic dishonesty was because the assignment was too difficult and they did not learn about the material well. All in all, most of the respondents understood about academic integrity, but they still tend to cheat. Thus, this study would help EFL students and teachers to maintain the academy integrity.DOI: 10.26905/enjourme.v7i2.8827